A PHONEMIC ANALYSIS BETWEEN ENGLISH AND INDONESIAN IN “HEAVEN” SONG - Anggraini, Leli; Sinaga, Kelly; Sirait, Febrianto; Barus, Reulina Arita; Siahaan, Veronika Febryanti; Sitanggang, Anita (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
This study compares and contrasts the phonetic systems of English and Indonesian in the lyrics to the song "Heaven." In order to teach students how to pronounce English with Indonesian phonemes, the research aims to compare and contrast the phonemes in song lyrics. Ten English consonant phonemes and ten Indonesian consonant phonemes are the focus of this study. A qualitative technique is used in the descriptive-contextual research methodology. Based on the types of phonemes, the technique design compares the phonemes in song lyrics written in English and Indonesian. The "Heaven" song lyrics, which are made up of 10 consonant phonemes, were discovered to share commonalities between the English and Indonesian phonemic systems. Ten consonants in the lyrics to the song "Heaven" represent the distinctions between the English and Indonesian phonetic systems.